Religious Coping For Schizophrenics At Upt Rehabilitasi Sosial Bina Laras Kediri - Hafil, Achmad Shodiqil; Arifa Ajie, Laro Iba (Jurnal Spiritual Healing, 2023)
Decreased productivity often occurs in people with schizophrenia. As a result, sufferers are more susceptible to stress, difficulties in skills, work and socializing with others. One of the efforts to help restore the mentality of schizophrenics is using spiritual healing. Spiritual methods can have a good impact on people with schizophrenia. Individuals with schizophrenia are more likely to show maladaptive coping, i.e. doing emotionally charged activities. Psychotherapy is carried out as a habituation of religious coping for schizophrenics through worship activities carried out by patients in rehabilitation to divert the focus of the stressor. This study used a type of descriptive qualitative research. Data collection techniques use observation, in-depth interviews, documentation, and measurement scales. Analytical techniques use 2 qualitative and quantitative research methods, namely: data reduction, data presentation, and conclusions. In order to strengthen the results of the study using validity and reliability test analysis techniques. The results of research on religious coping through worship activities of schizophrenics show that there are 2 dimensions of religious coping that dominate from schizophrenic patients, namely: The dimension of searching for meaning and control. Schizophrenics in the search for meaning in accordance with religious beliefs are overcoming problems through religious assistance. Then in controlling control, schizophrenics overcome problems actively, including: praying, telling stories, not bothering others, apologizing, patience, resignation, and istighfar. Despite having limitations, sufferers are able to follow spiritual behavior in the form of worship to God. The style or concept of religious coping with schizophrenics after doing worship activities uses a collaborative style, namely carrying out activities that involve God and individuals, sufferers close to religious leaders, and collaborating between effort (ikhtiyar) and praying